2015
DOI: 10.1002/cctc.201402781
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Nanoparticles Supported on Fibrous‐Structured Silica Nanospheres (KCC‐1): An Efficient and Selective Catalyst for the Transfer Hydrogenation of Alkenes

Abstract: An efficient palladium catalyst supported on fibrous silica nanospheres (KCC‐1) has been developed for the hydrogenation of alkenes and α,β‐unsaturated carbonyl compounds, providing excellent yields of the corresponding products with remarkable chemoselectivity. Comparison (high‐resolution TEM, chemisorption) with analogous mesoporous (MCM‐41, SBA‐15) silica‐supported Pd nanocatalysts prepared under identical conditions, demonstrates the advantage of employing the fibrous KCC‐1 morphology versus traditional su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 103 publications
3
42
0
Order By: Relevance
“…S27g). 32 Similarly, Al-MIL-53, Al-MIL-53-NH 2 and Al-MIL-53-NH-RNH 2 were prepared as alternative MOF catalysts for investigation. The morphologies of aminotagged MOFs were retained according to SEM images (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S27g). 32 Similarly, Al-MIL-53, Al-MIL-53-NH 2 and Al-MIL-53-NH-RNH 2 were prepared as alternative MOF catalysts for investigation. The morphologies of aminotagged MOFs were retained according to SEM images (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[53] In an early approach,S rivastava et al have reported the incorporation of Ti + 4 and Al + 3 ions in mesoporousS BA-15s ilica to create acidic surfaces ites. [54] The same materials were functionalized with basic moieties by grafting primary amines and aromatic amines such as imidazole, guanidine, and adenine.…”
Section: Heterogeneous Catalystsmentioning
confidence: 99%
“…Following reduction, its interaction with the NPs promotes dispersion and prevents sintering and leaching. It has been employed for the preparation of well‐spaced and uniformly dispersed Au nanoparticles on mesoporous silica, as well as for Pd, Ag, and Ru nanoparticles on the surface of KCC‐1 and on other supports . Au NPs prepared on MCM‐41 without amino‐functionalization of the surface showed a very broad size distribution and a high tendency towards sintering .…”
Section: Resultsmentioning
confidence: 99%
“…These features have been exploited for the preparation of highly active catalysts and CO 2 sorbents . We have previously demonstrated that Pd NPs supported on amino‐functionalized KCC‐1 were more accessible for interaction with CO and H 2 than on analogous amino‐functionalized traditional supports such as MCM‐41 and SBA‐15 . This result was found to have a remarkable impact on the catalytic performance of the supported species.…”
Section: Introductionmentioning
confidence: 99%